The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12055-011-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

Sternal wound infection following open heart surgery: appraisal of incidence, risk factors, changing bacteriologic pattern and treatment outcome

Abstract: Background The incidence of Sternal wound infection as reported worldwide is 0.43-2.3% [1-7]. The incidence is low and has serious effects on the patients in terms of the morbidity, hospital stay, cost as well as mortality. This study proposes to identify the risk factors, changing bacteriologic and the treatment outcomes. Methods 6492 consecutive patients who had median sternotomy for open heart surgery in the adult unit were retrospectively analysed (using SPSS10.0 window software) between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…It was revealed that swab and tissue cultures were positive in 82% of patients [22,23]. Superficial swab cultures were predictive of the pathogen in 75% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that swab and tissue cultures were positive in 82% of patients [22,23]. Superficial swab cultures were predictive of the pathogen in 75% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Good aseptic technique, judicious use of antibiotics, diathermy and good surgical techniques may contribute to a low incidence of sternal wound infection. 8 Supportive thorax vests and counseling also help to prevent mechanical sternal failure. 9 Our experience and that of others suggests that SW also has positive effects on sternal wound healing, reducing PSWC incidence and severity.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of DSWI as reported in the literatures is between 0.2-3.6% [1,13,14] and this can be higher especially when the following risk factors like age, diabetes mellitus, obesity, Hypertension, postoperative mechanical ventilation, and early surgical re-exploration, and some surgical techniques such as double harvest of Internal thoracic artery(ITA) in pedicled fashion ;combined valve and coronary artery bypass graft are adopted [15]. In the preoperative period, parameters like diabetes mellitus, COPD and preoperative renal insufficiency were independent risk factors for postoperative sternal complications [16,17].…”
Section: The Epidemiologymentioning
confidence: 94%
“…Deep Sternal Wound Infection (DSWI) is a rare but one of the challenging problems that can occur after open heart surgery ,especially with the management of defect; causing prolonged hospitalization, increased hospital costs, and increased morbidity and mortality [1][2][3][4][5][6]. There have been many novel surgical approaches that are geared toward the provision of adequate covers for the defects, as may occur in many cases; especially after extensive debridement [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%